Fulfillment of Bawean Electricity with a Hybrid Renewable Energy System using HOMER - Wijaya, Fiqih Akbar; Triyogi, Galih Wicaksono; Nugraha, Rizhal Ade; Warto; Priyono, Bambang (Journal of Advanced Technology and Multidiscipline, 2024)
Access to energy and electricity drives the economy, including industrial activities in isolated areas. Currently, the shrimp industry on Bawean (an isolated area) is facing the problem of many unserved power needs. Thus, this study aims to design hybrid renewable energy for the productive sector. There are two configurations, namely configuration 1 (PV SYSTEM, WIND TURBINE SYSTEM, GRID, BESS) and configuration 2 (PV SYSTEM, GRID, BESS), which find the potential for solar and wind radiation very suitable for renewable energy sources. Thus, based on the HOMER simulation, the best alternative solution is configuration 1 which utilizes PV SYSTEM (8.9 MW), 2 Wind Turbine System (1.6 MW), and 3 BESS, resulting in the lowest LCOE value of 0.137 $/kWh. The results of configuration 1 can meet the electricity needs of Bawean Island and shrimp ponds with the lowest LCOE value, so it can potentially increase productive sectors such as shrimp ponds.